Implementasi Metode NLP Dalam Pembuatan Chat Bot Telegram - Radi Alpiyanto; Muhammad Fitra Fajar Rusamsi; Yuyun Umaidah (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2023)
In the current digital era, the use of chat bots has become increasingly popular, especially oninstant messaging platforms like Telegram. To create a better user experience, accurate andresponsive understanding of user messages is necessary. In this regard, Natural LanguageProcessing (NLP) plays a crucial role. The goal of this research is to implement NLP methods inthe development of a Telegram chat bot using an appropriate and effective approach. In thisimplementation, experiments and testing are conducted to ensure the functionality andresponsiveness of the bot. Testing involves sending messages to the bot and evaluating the resultsof NLP processing and bot responses. During this process, enhancements and improvements aremade to enhance the bot's ability to understand and respond to user messages more effectively.NLP methods are applied in message handling. Entity recognition is used to identify importantinformation such as names, locations, or dates from user messages. Intent understanding isperformed to determine the intentions or goals behind received messages. Natural languageprocessing is used to analyze sentiment, keywords, or language structure in messages. Based onthe results of NLP processing, the bot provides appropriate responses to users through theTelegram bot API.